2011
DOI: 10.1111/j.1365-3164.2011.01001.x
|View full text |Cite
|
Sign up to set email alerts
|

Equine atopic skin disease and response to allergen‐specific immunotherapy: a retrospective study at the University of California‐Davis (1991–2008)

Abstract: This retrospective study reports on the clinical presentation of equine atopic skin disease and evaluates response to treatment with allergen-specific immunotherapy (ASIT) based on intradermal testing and/or serum testing. Computerized medical records from January 1991 to December 2008 yielded 54 horses included in the study. Presenting clinical signs (CS) included urticaria (n=28), pruritus (n=8) or both (n=18). Forty-one of 54 horses received ASIT, and response to ASIT (n=32) was evaluated via telephone surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0
2

Year Published

2013
2013
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 21 publications
4
40
0
2
Order By: Relevance
“…In general, approximately 70% of atopic horses improve with ASIT (Stepnik et al . ); other researchers have reported even better results, albeit in a noncontrolled report (Tallarico and Tallarico ).…”
Section: Allergiesmentioning
confidence: 84%
See 2 more Smart Citations
“…In general, approximately 70% of atopic horses improve with ASIT (Stepnik et al . ); other researchers have reported even better results, albeit in a noncontrolled report (Tallarico and Tallarico ).…”
Section: Allergiesmentioning
confidence: 84%
“…However, a full 12 months of ASIT should be given before fully evaluating its effectiveness, and veterinarians should maintain consistent communication with the client to monitor the progress of the treatment and to encourage the owner to continue with the injections for the full year. While in other domestic species it is thought that most patients will need to be maintained on the injections for life, this may not be true in the horse, as some horses had the ASIT injections stopped and did not relapse (Stepnik et al 2012). In general, approximately 70% of atopic horses improve with ASIT (Stepnik et al 2012); other researchers have reported even better results, albeit in a noncontrolled report (Tallarico and Tallarico 1998).…”
Section: Fig 3: Atopic Dermatitis Causing Urticaria and Facial Pruritmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Horses of a wide range of ages have been diagnosed with atopy. 48 No study has found any breed, age or sex predilections.…”
Section: Alopecic Dermatoses Atopymentioning
confidence: 96%
“…Urticaria, both pruritic and nonpruritic, is a reported common clinical sign. 47,48 Alopecia, self-trauma, and pitting edema are also relatively common. Lesions are most common on the face, pinnae, trunk, and distal part of the legs.…”
Section: Clinical Presentationmentioning
confidence: 98%